2000
DOI: 10.1590/s0100-879x2000000700015
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of policosanol on atherosclerotic lesions in rabbits with exogenous hypercholesterolemia

Abstract: Policosanol is a mixture of higher aliphatic alcohols purified from sugar cane wax, with cholesterol-lowering effects demonstrable in experimental models and in patients with type II hypercholesterolemia. The protective effects of policosanol on atherosclerotic lesions experimentally induced by lipofundin in rabbits and rats and spontaneously developed in stumptail monkeys have been described. The present study was conducted to determine whether policosanol administered orally to rabbits with exogenous hyperch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 27 publications
1
25
1
3
Order By: Relevance
“…Policosanol is the generic term used for a mixture of long-chain aliphatic primary alcohols (C24-C34), originally isolated from sugar cane (Saccharum officinarum L.) wax (Arruzazabala et al, 2000;Rodriguez-Echenique et al, 1994). Policosanol can also be extracted from a variety of other natural sources such as bee wax, rice bran and wheat germ Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Policosanol is the generic term used for a mixture of long-chain aliphatic primary alcohols (C24-C34), originally isolated from sugar cane (Saccharum officinarum L.) wax (Arruzazabala et al, 2000;Rodriguez-Echenique et al, 1994). Policosanol can also be extracted from a variety of other natural sources such as bee wax, rice bran and wheat germ Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 15% is made up of other alcohols, namely, tetracosanol, heptacosanol, docosanol, nonacosanol, and tetratriacontanol, which are the minor components. 16 Several reports, including many clinical trials, have shown that policosanols have significant health-promoting activities such as the reduction of lipid levels, [17][18][19][20][21] platelet aggregation reduction, 22 antiviral activity, 23 reduction of prostate enlargement, and relief of intermittent claudication. 24 In contrast, there are conflicting findings about the efficacy of policosanol, particularly with regard to lowering lipid levels.…”
mentioning
confidence: 99%
“…Policosanol, a mixture of primary aliphatic alcohols originally derived from sugarcane wax (Saccharum officinarum) (Janikula, 2002), in which octacosanol (63%), triacontanol (13%) and hexacosanol (6%) prevail (Gouni- Berthold et al, 2002), effectively improves serum lipid profiles. This effect was shown in animal models (Menéndez et al, 1996;Arruzazabala et al, 2000), healthy human subjects (Hernández et al, 1992), and patients with either type II hypercholesterolemia (Pons et al, 1992;Batista et al, 1996;Mas et al, 1999;Castaño et al, 2001), type II diabetes (Torres et al, 1995;Crespo et al, 1999), or postmenopausal women (Castaño et al, 2000). Interestingly, 10 mg of this mixture had similar efficacy to an equivalent dose of statins in lowering the serum LDL concentrations Prat et al, 1999), and its supplementation caused a significant increase in the fecal excretion of neutral and acidic sterols in hamsters (Ng et al, 2005), whereas octacosanol administration to humans decreased bile acid concentration in feces (Keller and Gimmler, 2008).…”
Section: Introductionmentioning
confidence: 73%